TRAVEL-TIMES MODELING OF REFLECTED WAVES FOR HORIZONTAL LAYER WITH STRONG ANISOTROPY - Prodaivoda, G.; Kuzmenko, P.; Vyzhva, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In the most seismic data processing software NMO-corrections for monothipic models of subsurface are considered as hyperbolic in the case if maximum offset does not exceed a depth to the reflecting surface. For anisotropic models are considered the presence of deviations from hyperbolic form of NMO-corrections even for small offsets. Awareness lack of the importance of non-hyperbolic moveout significantly reduces the quality of seismic data and the interpretations accuracy, especially for data derived using long-offset acquisition scheme. This article discusses the effect of geological symmetry influence of layer on a form of quasi P-wave travel-times for models with thick horizontal boundaries. Elastic modulus of layers are similar as real and identified using seismic methods in sedimentary strata. The paper describes the results of tests the methods and algorithms of travel-times computation for quasi P-wave in the case of horizontally layered medium with triclinic and orthorhombic symmetry. The algorithm is based on the solving task of reflection and refraction waves on a plane interface with two anisotropic layers. To determine the reflected and refracted rays used the Snell's law as equal to the tangential component of the boundary of the refraction vectors (incident, reflected, refracted waves). For finding the refraction projection of the reflected wave on the normal to the reflection surface is used the equation of refraction. For models with triclinic and orthorhombic symmetry maps of travel-times isochrones has azimuthal dependence, the location of extreme values adheres to existing elements of symmetry, in particular for models with orthorhombic symmetry to symmetry planes and axes of the second order. For the first time on the real elastic modulus for shale rocks was investigated that the symmetry of the travel-times surface of horizontally layered medium adheres to the elastic symmetry of the shale layer. It was found that long-offset travel-times of reflected waves provide an opportunity to assess the symmetry of layer and determine the nature of the azimuthal anisotropy of seismic velocities. The developed approach opens up wide possibilities for the investigation of complex seismic models in which non-hyperbolic dependence of NMO-corrections determined by the dip and curvature of reflectors, as well as heterogeneity of geological media.
Keywords: travel-times of reflected waves; anisotropy; symmetry; nonhyperbolity